2021
DOI: 10.1145/3485532
|View full text |Cite
|
Sign up to set email alerts
|

How statically-typed functional programmers write code

Abstract: How working statically-typed functional programmers write code is largely understudied. And yet, a better understanding of developer practices could pave the way for the design of more useful and usable tooling, more ergonomic languages, and more effective on-ramps into programming communities. The goal of this work is to address this knowledge gap: to better understand the high-level authoring patterns that statically-typed functional programmers employ. We conducted a grounded theory analysis of 30 programmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…That said, GT is an established and popular method in Software Engineering research [Stol et al 2016], and recently [Lubin and Chasins 2021] employed Constructivist GT [Charmaz 2006] to develop a deeper understanding of how statically-typed functional programmers write code. Which is why I recommend building a grounded theory of "How Rust Programmers Write Code".…”
Section: Grounded Theorymentioning
confidence: 99%
“…That said, GT is an established and popular method in Software Engineering research [Stol et al 2016], and recently [Lubin and Chasins 2021] employed Constructivist GT [Charmaz 2006] to develop a deeper understanding of how statically-typed functional programmers write code. Which is why I recommend building a grounded theory of "How Rust Programmers Write Code".…”
Section: Grounded Theorymentioning
confidence: 99%
“…Recent work has broadened scope to develop theories about how programmers read functional programs [Marceau et al 2011a], leverage the type system during development [Lubin and Chasins 2021], and solve problems with higher-order functions [Rivera and Krishnamurthi 2022].…”
Section: Related Workmentioning
confidence: 99%
“…Apart from being a tool for correcting syntax errors, it has been suggested that compilers can also serve as psychological reassurance [21,23], and also as a means to correct mental models of the problem domain and as a dynamic task-direction mechanism [27].…”
Section: Prior Workmentioning
confidence: 99%